Difficulty in accessing basic sanitation in the riverside regions of the State of Pará and its consequences on the quality of water resources: a case study from Ilha das Onças (Research, Society and Development, 2021)
Despite the universalization of basic sanitation being an objective foreseen by Brazilian legislation, it is still a difficult objective to be achieved. When it comes to the North region and especially areas where traditional communities reside, this is an even greater challenge. The riverside populations or communities correspond to the families that live on the banks of the rivers. Such communities present a marked degree of isolation and social exclusion due to their respective locations, which are predominantly far from large urban centers. Thus, difficulty in accessing public policies is maximized, also reflecting the very low rates of basic sanitation services in these regions. This study aimed to establish a diagnosis of the current situation of basic sanitation in the riverside region of Ilha das Onças located in the municipality of Barcarena-PA. For this, a quali-quantitative survey was carried out, adopting the application of questionnaires as a method to obtain the residents' responses and, later, a statistics was performed using the Excel software. The results show that 78% do not have access to basic sanitation and that a large part of the population has no idea of ​​its importance for health.